La souffrance morale au travail - Phongsavanh, Thitphrachanh Kay (Université d'Avignon, 2015)
La souffrance morale au travail a déjà été évoquée par le docteur Villermé au 19ème siècle, elle renaît de ses cendres à chaque fois que les périodes difficiles de l’économie ou de la politique se présentent. La compréhension des mécanismes psychologiques sont nécessaires pour que le droit puisse attribuer une qualification juridique la plus adaptée. Le dommage qui est causé au travailleur doit, alors, trouver une indemnisation correspondant aux préjudices. La création d’un poste de préjudice spécifique dédié aux troubles psychologiques est une démarche que je me suis efforcé de mettre en place pour que sa reconnaissance en tant que lésion soit appréciée au même titre qu’une blessure physique. Le « psychomètre » (échelles d’évaluations des troubles psychologiques) est reposé sur un ensemble éprouvé de méthodes et de techniques scientifiques. A l’heure actuelle, ces méthodes nous permettent d’apprécier et d’évaluer avec une grande précision la souffrance psychologique du travailleur au travail. La détermination du degré de la souffrance, de l’intensité et de l’incapacité du salarié par un expert nous autorise à affecter une indemnisation correspondant à la lésion en se fondant sur un barème spécifique que j’ai développé pour les troubles psychologiques.Mais, la prévention des risques doit être la démarche de toutes les entreprises et les partenaires sociaux pour supprimer ou diminuer les risques psychosociaux. De ce fait, les compétences des spécialistes du monde médical, de l'ergonomie, du droit, etc. doivent être rassemblées pour atteindre les objectifs. Le rôle de l’employeur, du CHSCT et de l’Institution Représentative du Personnel est essentiel dans la démarche de la prévention des risques professionnels. The moral suffering in the workplace has already been mentioned by Dr. Villermé in the 19th century, it rises from the ashes whenever difficult times in the economy or politics arise. Understanding the psychological mechanisms are required for the law to assign the most appropriate legal qualification. The damage that is caused to the worker must then find a compensation corresponding to the damage. The creation of a specific prejudice station dedicated to psychological disorders is an approach that I have tried to put in place for its recognition as a lesion is appreciated just as a physical wound. The ''psychometer'' (scales of assessments of psychological disorders) rested on a proven set of methods and scientific technics. At present, these methods allow us to assess and evaluate with great precision the psychological suffering of the worker at work. The degree of pain, intensity and disability of the employee by an expert allows us to assign a compensation for the damage based on a specific schedule that I developed for psychological disorders. Thus , the prevention of risks should be the approach of all social enterprises and the partnerships (Unions and employers). As a result, the skills of experts from the medical world, ergonomics, law, etc. must be collected to achieve the objectives. The role of the employer, the CHSCT and the Institution Staff Representative is essential in the process of prevention of occupational hazards.
Keywords: Harcèlement; Indemnisation; Risques professionnels; Risques psychosociaux; Stress; Stress lié au travail; Violence en milieu de travail; Violence psychologique

La mobilité du salarié - Brier, Henrik De (Université d'Avignon, 2015)
Après la Seconde Guerre mondiale, une volonté s’exprime de construire la paix sur une mise en commun des intérêts économiques. La paix entre les nations a donc pour conséquence une internationalisation des échanges économiques. Nous sommes alors passés d’une volonté politique à une réalité économique. Les entreprises se sont développées en même temps qu’elles ont dû faire face à une nouvelle concurrence. Les travailleurs salariés sont devenus des maillons indispensables, mais aussi, quelque part, des pions, sur ce nouvel échiquier économique. Les entreprises sont donc, de plus en plus, à la recherche de souplesse dans la gestion de leurs effectifs. Face à la prétendue rigidité du contrat de travail, l’on assiste, notamment, à une montée en puissance de l’accord collectif, dans le but de flexibiliser la relation de travail ; la mobilité s’entend, alors, de plus en plus, comme une mobilité sur le marché du travail, et non plus seulement dans l’entreprise. Ainsi, naît un besoin indispensable de sécuriser la mobilité de ces salariés, notamment à travers le contrôle des trajectoires professionnelles, en créant, notamment, un véritable droit de la formation professionnelle. After the Second World War, a desire to build peace based on common economic interests is formulated. Consequently, this shared wish of peace influences economic exchanges by making them international. We reach now a new step: passing from a political willpower to an economic reality. The companies had to manage their own development facing new competitors at the same time. Workers became essential links, but also, paws on this new economic chess game. Hence, the companies look progressively for more flexibility to manage their human resources. In response to the alleged rigidity of the employment contract, the society is witnessing an important and increasing spread of collective agreement, providing flexibility in the relationship between employer and employee at work. In this way, the mobility is more and more thought as mobility of labor market, and not just as a mobility within individual establishments. Thus, ensuring the safety of employee’s mobility becomes an essential need, particularly through the control of career paths, creating a genuine right of vocational training.
Keywords: Formation professionnelle; Mobilité; Mobilité professionnelle; Parcours professionnel; Sécurisation

Le licenciement économique dans les groupes de sociétés - Zarba, Catherine (Université d'Avignon, 2015)
Depuis le développement du capitalisme, la nécessité de créer un droit des groupes est apparue. Cette nécessité est corroborée par le fait qu’aujourd’hui, un salarié sur deux appartient à un groupe de sociétés. De plus, à l’aune de la mondialisation du contexte économique, le nombre de licenciements ne cesse d’augmenter. Certains groupes ont besoin de licencier pour sauvegarder leur santé économique, tandis que d’autres souhaitent prospérer. Ces derniers vont même jusqu’à l’abandon de leur filiale pour augmenter leur profit. Le législateur a institué une procédure de licenciement économique, applicable au groupe de sociétés, qui participe à une prévention des licenciements. Parallèlement, il a construit peu à peu un droit applicable à ce dernier dans le cadre d’une procédure individuelle et collective. Il a institué d’une part, l’obligation de rapatriement des salariés mis à disposition d’une filiale étrangère et, d’autre part, l’obligation de constituer un comité de groupe. Enfin, le groupe est tenu de contribuer à l’élaboration du plan de sauvegarde de l’emploi de ses filiales en fonction de ses moyens. Par ailleurs, l’existence d’un véritable droit des groupes dans le cadre d’une procédure de licenciement économique est confirmée par la position de la jurisprudence. En effet, le juge social est intervenu activement pour construire ce droit des groupes de sociétés. Tout d’abord, il a dégagé une obligation de reclassement élargie au groupe participant à l’édification de ce droit spécifique. Puis, la Chambre sociale a souhaité imputer une responsabilité au groupe en qualifiant la société donneuse d’ordre de coemployeur, ce qui permet de sanctionner le groupe de manière adaptée. Il existe donc un droit des groupes dans le cadre de la procédure des licenciements économiques participant à leur prévention, et intervenant lors dans leur mise en œuvre.
Keywords: Co-employeur; Economic redundancy; Group of compagnies; Groupe de sociétés; Licenciement économique; Licenciements économiques; Reclassement; Reclassification; Secteur d'activités

L'exercice du droit de grève dans le secteur privé - Vervoort, Maxence (Université de Nice Sophia-Antipolis, 2015)
A mi-chemin entre le droit et la pratique, le droit de grève demeure principalement le produit d’une jurisprudence ouverte aux influences extérieures. Loin d’être enfermé dans une morale théorique et immobile, le droit de grève rayonne donc par son dynamisme et sa facilité à répondre aux défis conjoncturels et structurels auxquels doit faire face l’entreprise. Dans ces conditions, comment est juridiquement façonné l’exercice du droit de grève ? Quelles sont les interactions réciproques et permanentes entre la jurisprudence et la pratique, qui confèrent à ce droit toute son effectivité ? Quelles sont les influences, juridiques et a-juridiques, qui viennent guider son exercice au quotidien ? Half way between the law and common practice , the right to strike is the result of a case law open to external influences. Far from being stuck in a theoritical and fixed ideology, the right to strike lies on dynamic grounds and on its ability to challenge the temporary and structural contexts that a company must cope with. In these conditions, how can the right to strike be legally shaped? What are the mutual permanent interactions between a case law and common practice which confers to this right its total effectiveness ? What are the legal and contextual influences that guides its daily practice ?
Keywords: Droit de grève; Droit du travail; France; Grèves et lock-out; Labour law; Private sector; Right to strike; Secteur privé

La modélisation multi-agent du marché du travail français - Goudet, Olivier (Université Paris 6, 2015)
Cette thèse présente un modèle multi-agent du marché du travail. Le modèle reproduit le fonctionnement du marché tant au niveau agrégé, qu'au niveau des principales catégories de main-d'œuvre, sur la base des décisions d'agents hétérogènes, entreprises et individus, qui interagissent. Les décisions reposent sur des calculs de profits et d'utilités et se font dans un contexte de rationalité limitée. La structure théorique sous-jacente sur laquelle repose les mécanismes décisionnels est le concept de \textit{recherche}. Nous appliquons ce cadre de modélisation pour étudier le marché du travail français en 2011. Le modèle est à l'échelle de 1/4700. Il est très détaillé au niveau des institutions du marché du travail qui ont une influence sur les décisions des agents. Le modèle est ensuite calibré par un algorithme puissant de façon à reproduire un grand nombre de cibles importantes du marché du travail. Le modèle ainsi calibré permet de faire émerger une comptabilité cohérente des flux bruts des individus entre les principaux états : emploi (avec la distinction CDD et CDI), chômage et inactivité. La simulation des flux permet de faire émerger différents schémas de mobilité et de caractériser la nature du marché du travail. Nous reproduisons la part importante de contrats à durée déterminée parmi les embauches et nous mettons en évidence la dualité du marché du travail français. La prise en compte des effets d'éviction de certaines catégories d'agents (les jeunes par exemple) par d'autres catégories d'agent est un des apports du modèle pour l'analyse du marché du travail. Nous avons enfin étudié une série de politiques économiques suivant différents indicateurs. Nous montrons qu'il est difficile de trouver une politique publique qui donne de bons résultats pour tous les critères et qui est bénéfique à la fois pour toutes les entreprises et tous les individus. Tout est affaire de compromis et de choix politique. This thesis presents an agent-based model of the labor market. The model simulates the market at the aggregate level and at the level of the principal manpower categories, on the basis of the decisions of heterogenous agents, firms and individuals, who interact. These decisions rely on computations of profits and utilities in a context of bounded rationality. The theoretical structure that underlies the decisions is the search concept. We apply this framework to the case of France in 2011. The model is at a scale of 1/4700. It is fairly detailed on the institutions of the labor market which constrain the agents’ decisions. Subsequently, it is calibrated by a powerful algorithm to reproduce a large number of variables of interest. The calibrated model presents a coherent accounting system of the gross flows of the individuals between the main states, employment, distinguishing open ended contracts and fixed duration contracts, unemployment and inactivity. The simulation of the gross flows enables us to analyse the patterns of mobility and to characterize the nature of the labor market under study, reproducing the high proportion of the fixed duration contracts in the hiring flows, and it points to a dualism of the French labor market. Modeling crowding out of some categories of workers (for instance the youths) by others is then a main contribution of the model to the labor market analysis. Finally, we study economic policies according to various indicators. We show that it is difficult to find a public policy which provides good results for all criteria and which is beneficial both for firms and individuals. It is all a question of compromise and political choice.
Keywords: AI; Artificial Intelligence; Calibration; Inteligência artificial; Intelligence Artificielle; Labor market; Logiciels; Marché du travail; Multi-agent system; Politiques publiques; Simulation; Simulation par ordinateur; Système complexe; Système multi-agent

L'apport du droit du travail à la théorie générale de l'acte juridique - Bento de Carvalho, Lucas (Université de Bordeaux, 2015)
Par les représentations qu’elle véhicule et les solutions qu’elle encourage, l’édification d’une théorie générale n’est jamais neutre au plan axiologique. Sa construction repose certes sur la connaissance du droit positif de lege lata, mais la mise en ordre qui en résulte demeure quant à elle intimement liée aux perceptions et aux convictions de l’interprète. C’est en ce sens que doit êtreabordée la question de l’apport du droit du travail à la théorie générale de l’acte juridique. La présente étude met en évidence le caractère protéiforme du phénomène envisagé, sans occulter les situations oùla discipline fait davantage figure de contre modèle que de véritable source d’inspiration. Adoptant un point de vue prospectif, cette recherche met en évidence les aspects de droit du travail susceptibles d’encourager la promotion d’une théorie de l’acte juridique marquée par le pluralisme. La matière contribue ainsi à souligner la variété des conditions dans lesquelles se forme la volonté de s’engager,tout comme la diversité de ses modes d’expression. Elle témoigne également d’une capacité certaine à traduire sur le terrain du Droit, afin de mieux les appréhender, l’altérité des rapports de force et la mutabilité des données factuelles qui accompagnent l’exécution des actes juridiques.
Keywords: Acte unilatéral; Actes juridiques; Actes unilatéraux; Apport; Bonne foi; Caducité; Cause réelle et sérieuse; Civil law; Contract law; Contracts regulations; Contractual freedom; Contrat; Droit commun; Droit du travail; Dépendance économique; Economic dependance; Economie du contrat; Implied terms; Labour law; Legal act; Liberté contractuelle; Loyaltie; Obligation de motivation; Ordre public; Power; Réforme du droit des contrats; Théorie de la cause; Théorie générale de l'acte juridique; Unfair terms; Unilateralism; Unilatéralisme

Regional Labour Standards in the SADC: Is It Possible, Given the EU Experience? - Smit, Paul (Journal of Law, Society and Development, 2015)
Globalisation and the increasing movement of capital and labour across international borders, with the exception of migrant workers who are facing major obstacles due to immigration laws, are creating a situation where laws in general and labour laws in particular are acquiring an international character. International bodies such as the United Nations, the International Labour Organisation and the European Union have adopted various international norms and standards to which most countries have agreed and which have established minimum international standards for basic universal human rights and worker rights. The Southern African Development Community is a transnational organisation that has also adopted certain basic norms and standards in its Treaty, Charter on Fundamental Social Rights and various protocols that are applicable to all citizens within the Community. In this contribution, the concept of transnational labour relations is considered. The different international approaches towards transnational labour relations are evaluated, as is the manner in which the European Union approached the integration of regional labour standards. The author seeks to establish what the Southern African Development Community can learn from the European Union’s experience and in what way a transnational labour relations system or regional labour standards regime for the Southern African Development Community can be established.
Keywords: Regional integration; Transnational labour relations (TNLR); international law; labour rights; regional labour standards; social rights

La perspective transfrontalière de l'emploi dans l'eurorégion Aquitaine-Euskadi - Brillant Etchemaite, Virginie (Université de Bordeaux, 2015)
L’objet de ce travail de recherche sur la perspective transfrontalière de l’emploi dans l’Eurorégion Aquitaine-Euskadi, est d’engager une réflexion à partir de la comparaison des ordres juridiques espagnol et français, sur les voies et les moyens juridiques susceptibles de permettre une certaine forme d’intégration des politiques de l’emploi à l’échelle eurorégionale, en dépassant deux séries d’obstacles : ceux inhérents à la coexistence de deux systèmes juridiques nationaux au sein d’un espace unique de type eurorégional, mais également ceux liés à la libre circulation des travailleurs, à la fois individus et citoyens. La démonstration de cette thèse s’opère en deux phases : une première phase descriptive et analytique suivie d’une seconde phase de modélisation. En premier lieu il s’agit d’exposer que les politiques nationales de l’emploi qui s’appliquent dans les zones frontalières qui forment l’Eurorégion Aquitaine-Euskadi, se caractérisent toutes deux, par une hégémonie étatique et une ambiguïté territoriale (Première partie).En second lieu, il est proposé d’envisager une évolution des politiques de l’emploi vers une « défronterisation » grâce à la mise en oeuvre du processus d’intégration (Deuxième partie). This research about the cross-border perspective of employment in the Euroregion Aquitaine- Euskadi, based on a comparison between the spanish and french legal systems, aims to analyze the ways and legal tools towards a certain form of integration of employment policies at euroregional scale. It supposes to get through two kinds of difficulties: those related to the coexistence of two national legal systems within a single euroregional space and those related to the freedom of movements of workers, as individuals and citizens. The first step of the research is a descriptive and analitical one; the second step proposes a form of modelisation. First, the thesis aims at describing the national employment policies wich are implemented in cross-border areas such as the Euroregion Aquitaine-Euskadi. Both of them are characterized by a State hegemony and by a complex organization of competences of local authorities. Second, it suggests an evolution of employment policies towards the neutralisation of the border effect thanks to the implementation of integration processes through experimental legal rules.
Keywords: Aquitaine (France); Coopération transfrontalière; Cross-border cooperation; Employment policies; Espagne; Expérimentation juridique; France; Intégration régionale; Intégration économique internationale; Legal experimentation; Pays basque (Espagne); Politique de l'emploi; Politiques de l'emploi; Regional integration

La Negociación Colectiva de los derechos sindicales del personal estatutario de los servicios de Salud - Garrido Heras, Antonia (Universitat Jaume I, 2015)
El derecho a la negociación colectiva en el ámbito de las relaciones de trabajo es probablemente una de las conquistas históricas más importantes de nuestro ordenamiento jurídico y tiene una fuerte conexión con los principios democráticos y sociales en los que este se apoya. Su reconocimiento inicial en la Constitución española de 1978 se hizo extensivo por vía legal, hace veinticinco años, a todos los funcionarios de las diferentes Administraciones públicas españolas, entre ellos al personal que actualmente se denomina estatutario de los Servicios de salud, que presta servicios en las instituciones sanitarias del Sistema Nacional de Salud. El ejercicio de este derecho colectivo ha permitido consensuar su normativa básica y los diversos aspectos de su régimen jurídico, entre ellos los derechos y garantías sindicales de que disponen sus representantes y las organizaciones sindicales para llevar a cabo libremente la acción sindical. El desarrollo de la normativa negociada del personal del Sistema Nacional de Salud se ha llevado a cabo de forma simultánea a la que ha permitido el aumento y diversificación de las prestaciones sanitarias públicas a los ciudadanos dentro del principio de universalidad de la asistencia sanitaria. La tendencia de las políticas legislativas actuales, sin embargo, no va en la línea de promocionar el ejercicio del derecho a la negociación colectiva para la determinación de las condiciones de trabajo de los empleados públicos, sobre todo por lo que se refiere a sus derechos sindicales. Asimismo, el principio de universalidad de las prestaciones ha desaparecido en virtud del Real Decreto Ley 16/2012, de 20 de abril. Una de las medidas de corrección del déficit público en las Administraciones españolas se ha dirigido en los últimos tiempos, con especial intensidad, a la reducción de los medios personales y materiales de que disponen las organizaciones sindicales para el desarrollo de la acción sindical. Estas políticas toman fuerza a raíz de la modificación del artículo 135 CE, en septiembre de 2011, que incorpora el principio de estabilidad presupuestaria, prohibiendo al Estado incurrir en un déficit estructural que supere el límite establecido por la Unión Europea. Este precepto fue desarrollado por la Ley Orgánica 2/2012, de 27 de abril, de Estabilidad Presupuestaria y Sostenibilidad Financiera, y a lo largo de ese año las CCAA aprueban Planes económico-financieros de ajuste, que incluyen, entre otras muchas, medidas de reducción de los derechos sindicales de los empleados públicos. La aprobación por el Gobierno del Estado del Real Decreto Ley 20/2012, de 13 de julio, dispone la supresión de todo lo acordado en materia de garantías sindicales de los empleados públicos y sujeta su regulación a lo estrictamente dispuesto en la normativa legal de aplicación: la LOLS, la LEBEP y el TRET. Desde su entrada en vigor se han concertado en determinadas Administaciones autonómicas, no en todas, Acuerdos de Adecuación a dicho Real Decreto Ley. En las conclusiones del trabajo se pone de relieve la pérdida de los derechos y garantías sindicales que han provocado estas medidas para las organizaciones sindicales implicadas, para los profesionales del Sistema Nacional de Salud y, por afectar a los principios en los que este se basa, también para el conjunto de la sociedad.
Keywords: Administració i dret; Derecho laboral; Negociación colectiva; Negocis; Servicios de Salud

Employee participation and voice in companies: a legal perspective - Botha, Monray Marsellus (North-West University, 2015)
Recently, South African company law underwent a dramatic overhaul through the introduction of the Companies Act 71 of 2008. Central to company law is the promotion of corporate governance: companies no longer are accountable to their shareholders only but to society at large. Leaders should direct company strategy and operations with a view to achieving the triple bottom-line (economic, social and environmental performance) and, thus, should manage the business in a sustainable manner. An important question in company law today: In whose interest should the company be managed? Corporate governance needs to address the entire span of responsibilities to all stakeholders of the company, such as customers, employees, shareholders, suppliers and the community at large. The Companies Act aims to balance the rights and obligations of shareholders and directors within companies and encourages the efficient and responsible management of companies. The promotion of human rights is central in the application of company law: it is extremely important given the significant role of enterprises within the social and economic life of the nation. The interests of various stakeholder groups in the context of the corporation as a “social institution” should be enhanced and protected. Because corporations are a part of society and the community they are required to be socially responsible and to be more accountable to all stakeholders in the company. Although directors act in the best interests of shareholders, collectively, they must also consider the interests of other stakeholders. Sustainable relationships with all the relevant stakeholders are important. The advancement of social justice is important to corporations in that they should take into account the Constitution, labour and company law legislation in dealing with social justice issues. Employees have become important stakeholders in companies and their needs should be taken into account in a bigger corporate governance and social responsibility framework. Consideration of the role of employees in corporations entails notice that the Constitution grants every person a fundamental right to fair labour practices. Social as well as political change became evident after South Africa's re-entry into the world in the 1990s. Change to socio-economic conditions in a developing country is also evident. These changes have a major influence on South African labour law. Like company law, labour law, to a large extent, is codified. Like company law, no precise definition of labour law exists. From the various definitions, labour law covers both the individual and collective labour law and various role-players are involved. These role-players include trade unions, employers/companies, employees, and the state. The various relationships between these parties, ultimately, are what guides a certain outcome if there is a power play between them. In 1995 the South African labour market was transformed by the introduction of the Labour Relations Act 66 of 1995. The LRA remains the primary piece of labour legislation that governs labour law in South Africa. The notion of industrial democracy and the transformation of the workplace are central issues in South African labour law. The constitutional change that have taken place in South Africa, by which the protection of human rights and the democratisation of the workplace are advanced contributed to these developments. Before the enactment of the LRA, employee participation and voice were much-debated topics, locally and internationally. In considering employee participation, it is essential to take due cognisance of both the labour and company law principles that are pertinent: the need for workers to have a voice in the workplace and for employers to manage their corporations. Employee participation and voice should be evident at different levels: from information-sharing to consultation to joint decision-making. Corporations should enhance systems and processes that facilitate employee participation and voice in decisions that affect employees. The primary research question under investigation is: What role should (and could) employees play in corporate decision-making in South Africa? The main inquiry of the thesis, therefore, is to explore the issue of granting a voice to employees in companies, in particular, the role of employees in the decision-making processes of companies. The thesis explores various options, including supervisory co-determination as well as social co-determination, in order to find solutions that will facilitate the achievement of employee participation and voice in companies in South Africa.
Keywords: CSR; Collective bargaining; Corporate Social Responsibility; Corporate governance; Corporate law; Disputes; Economic democracy; Employee participation; Empowerment; Fairness; Industrial democracy; Joint decision-making; Labour law; Matters of mutual interest; Shareholders; Social justice; Stakeholders; Workplace forums

Partir du droit pour aborder le problème de l’économie informelle : réflexions sur le projet d’une norme internationale à travers deux « économies informelles » au Togo - Panier, Élise (Sociologie et sociétés, 2015)
En partant du récent projet de norme de l’OIT visant à favoriser la formalisation de l’économie informelle, cet article propose d’interroger la démarche institutionnelle à travers une réflexion sur le droit comme critère d’intelligibilité de la catégorie de l’informel. Sur la base d’une enquête réalisée au Togo, cette contribution présente les modalités nombreuses et complexes des manifestations du droit du travail et du droit de l’activité économique dans les deux espaces d’informalité du travail que sont la zone franche d’exportation et le secteur dénommé informel au Togo. Entre surformalisation spécifique et im-pénétration publique ou syndicale dans un cas, et intervention publique et syndicale relativement quotidienne dans l’autre, la manière de vouloir faire de l’économie informelle un objet d’intervention global, en distinguant l’emploi informel des unités économiques, n’est pas sans soulever des questions sur la pertinence de la démarche et le rôle de ce concept souvent critiqué mais, paradoxalement, d’usage permanent.
Keywords: Derecho trabajo; Droit du travail; Economie informelle; Free export zone; Informal economy; Labour law; Rights; Togo; Zona franca exportación; zone franche d’exportation

Labour rights and working conditions in corporate codes of conduct: an assessment of the legal dimension, in different national contexts, of selected multinational corporations’ corporate social responsibility commitments - Tiemeni, Thierry Galani (University of the Western Cape, 2015)
At the heart of this thesis is the notion of Corporate Social Responsibility (CSR), an innovative concept deep-rooted in the globalisation phenomenon. The notion of CSR entails the much-debated duty of businesses, not only to comply with international and local standards in terms of, inter alia, labour rights and working conditions, human rights and environmental protection, but also to be at the forefront of voluntary and uplifting actions geared toward addressing societal issues and concerns. For corporations, it is about moving from the traditional approach of business as an activity with the sole purpose of realising profit towards acknowledging the need to integrate societal and environmental issues and concerns into their business purposes. The thesis examines selected multinational corporations’ (MNC) approaches to CSR as contained in their codes of conduct, in an effort to reach a comprehensive understanding of the purpose, interest and practices of businesses engaging in CSR activities. Particular attention is given to the analysis of labour orientated measures implemented by selected MNCs as they undertake to voluntarily act as proponents of the theory of the necessity of socially responsible businesses. The aim is to comparatively assess the legal dimension and the relevance, in different countries, of these MNC CSR commitments. The first part of the thesis is theoretical and has the purpose to present a comprehensive analysis of CSR against the current legal framework, at a global scale and within the context of selected countries. The thesis will explore the notion of CSR in order to present its definition and characteristics, briefly retrace its history, differentiate it from related and/or similar concepts, and finally assess the extent of its introduction and adaptation into various national and international institutional frameworks. Even though initially addressing the issue of CSR in the current legal framework as a whole, the scope of the thesis will ultimately be reduced to focus only on labour-related aspects of CSR. The aim of the thesis is to assess MNC’s CSR commitments, and subsequently highlight the interaction between CSR, labour and employment legal frameworks (at national and international level) and the effective implementation of labour rights and working conditions as observed in the context of different countries. More importantly, the thesis will also include a comparative analysis of CSR principles included in selected MNC codes of conduct, in order to assess the extent of their compliance with national labour legislation, international labour standards, as well as the standards and principles set by national and international CSR instruments and institutions. The purpose of such an exercise is to thoroughly assess the impact of a national context - in terms of national legal, economic, social and industrial framework - on the legal dimension, and the relevance of MNCs CSR commitments. A crucial argument developed in the thesis refers to the fact that MNC codes of conduct may have the potential to impact on labour rights and working conditions of a MNC across the different countries into which the MNC operates. Finally, considering the fact that as a topic CSR is a potentially controversial subject, it is necessary to point out, from the onset, that the thesis engages with the subject from a critical perspective. The approach therefore entails critically analysing and discussing MNC commitments and practices as observed in different countries, so as to be able to ascertain and comprehend the impact of a national context on the content, the relevance and the legal dimension of MNC codes of conducts
Keywords: Code of conduct; Corporate Social Responsibility; Labour rights; Multinational corporations; Working conditions